A influência do radiojornalismo em comunidades quilombolas: o caso da comunidade tradicional quilombola de Santa Maria das Mangueiras, de Dois Irmãos, estado do Tocantins - Dias, Marciley Alves (2023)
Radio journalism is a form of communication that has great appeal in remote communities, a view that is demonstrated in the present study. Thus, the general objective of this research is: to understand the perception of the Quilombola Community of Santa Maria das Mangueiras (Dois Irmãos - TO) about the role of radio journalism. To reach this objective, the following specific objectives are allowed: to describe the profile of the Quilombola Community Santa Maria das Mangueiras; analyze how the Community accesses and consumes information; check how the radio is present in the Community; and, to verify the confidence that the Community gives the news that arrives via radio. The approach of this research is qualitative. From an operational point of view, a documentary research was carried out with the purpose of knowing the history of the Quilombola Community of Santa Maria das Mangueiras. In addition, a semi-structured interview was carried out with ten residents of the Community. subsequently, data from these interviews were analyzed based on the creation of four distinct categories, the first of which concerns history; the second is related to the way in which information is consumed; the third concerns the presence of radio in the Community; and the fourth refers to the relationship between the members and the radio. As a result, it is felt that the radio is of great importance for the Quilombola Community, since the residents have a relationship of trust with it. The radio is so reliable that it is capable of confirming the news that residents may receive from other sources. In addition, there is a great affection of the residents with respect to the radio.